Prospective Evaluation of Feline Sourced Platelet-Rich Plasma Using Centrifuge-Based Systems - Ferrari, Jonathan T.; Schwartz, Pamela (Frontiers in Veterinary Science, 2020)
Objective: To evaluate the hematologic components of platelet-rich plasma (PRP) generated using feline blood with two commercially available centrifuge-based systems1,2. Materials and methods: Twenty healthy adult cats were enrolled in this prospective study from November 2018 to January 2019. Feline blood samples were obtained for analysis of whole blood (WB) cellular components and preparation of PRP product. PRP was prepared using two commercial systems and complete blood count (CBC) testing was performed on both WB and PRP samples. The cellular composition of the PRP product was compared to the WB sample for each patient. Results: Both systems showed significant decrease of median RBC concentration in PRP products compared to WB samples (P = 0.002 for both systems). System 1 significantly decreased median WBC concentration (P = 0.002). System 2 decreased WBC concentration, though statistical significance was not reached (P = 0.63). Median platelet concentration was decreased by 3% using System 1, and increased by 187% using System 2. Platelet aggregation presented a challenge with 8/20 (40%) of samples demonstrating platelet aggregation. Clinical Relevance: Commercial systems available for generation of PRP may be useful for creating a feline sourced product and in this study showed promise in decreasing RBC and WBC concentration. Neither system tested achieved 2-5 times platelet concentration from baseline. Platelet aggregation presented a significant obstacle to reliable generation of PRP products using feline blood. This treatment modality may be particularly beneficial for feline patients with osteoarthritis and soft tissue injuries, though first characterizing the PRP product made using feline blood is critical to validate its use in further clinical studies.